2021
DOI: 10.1159/000519784
|View full text |Cite
|
Sign up to set email alerts
|

The Pentose Phosphate Pathway in Cancer: Regulation and Therapeutic Opportunities

Abstract: <b><i>Background:</i></b> Tumorigenesis is associated with deregulation of nutritional requirements, intermediary metabolites production, and microenvironment interactions. Unlike their normal cell counterparts, tumor cells rely on aerobic glycolysis, through the Warburg effect. <b><i>Summary:</i></b> The pentose phosphate pathway (PPP) is a major glucose metabolic shunt that is upregulated in cancer cells. The PPP comprises an oxidative and a nonoxidative phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 138 publications
0
31
0
Order By: Relevance
“…The PPP, as a branch of glycolysis for maintaining biosynthesis and controlling redox homoeostasis, is a fundamental component of cellular metabolism [ 5 , 6 ]. It has been reported that enhanced activity of the PPP provides materials for anabolism like pentose phosphates, to use their high rate of biosynthesis, including DNA synthesis, which is considered to be critical for tumour progression and drug resistance [ 5 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPP, as a branch of glycolysis for maintaining biosynthesis and controlling redox homoeostasis, is a fundamental component of cellular metabolism [ 5 , 6 ]. It has been reported that enhanced activity of the PPP provides materials for anabolism like pentose phosphates, to use their high rate of biosynthesis, including DNA synthesis, which is considered to be critical for tumour progression and drug resistance [ 5 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pentose phosphate pathway (PPP), as a committed step of glucose metabolism, which is required for maintaining the cellular redox state. Cancer cells modulate the flux of the PPP depending on the particular metabolic demand [ 5 , 6 ]. Activated PPP generates high levels of NADPH and ribonucleotides in cancer cells, which promotes pancreatic tumorigenesis and metastasis [ 7 9 ], emphasising the vital role of PPP in pancreatic cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…GBM cells are characterized by a preference for aerobic glycolysis rather than oxidative phosphorylation, which is more active in normal cells [ 33 , 34 ]. However, in addition to elevated glycolysis, proliferating and cancer cells must also divert carbon from glycolysis to the pentose phosphate pathway (PPP) to satisfy their anabolic demands and maintain the redox homeostasis of cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the oxidative branch of the PPP has already been studied in GBM by correlating enzyme expression with tumor aggressiveness and patient survival and proposing their targeting as a promising therapeutic target, the nonoxidative branch of the PPP has never been sufficiently evaluated in GBM. However, there are studies on other cancer types that confer an important role in tumor progression on the nonoxidative branch of the PPP and overexpression of its enzymes mainly due to increased proliferation of cancer cells [ 15 , 21 , 34 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, pentose phosphate pathway (PPP) has fundamental functions which were essential for cell nutrients metabolism and macromolecular biosynthesis. 15 , 16 , 17 , 18 , 19 First of all, PPP pathway generates ribulose‐5‐phosphate for nucleotide biosynthesis. Seconds, PPP pathway generates numerous NADPH, which is involved in macromolecular synthesis.…”
Section: Discussionmentioning
confidence: 99%